BIOACCUMULATION AND ENZYME ACTIVITY INHIBITION OF PROFENOFOS IN JAPANESE MEDAKA (ORYZIAS LATIPES TEMMINCK AND SCHLEGEL, 1846) - Pascual-Alburo, Rosalyn L. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 2, 2015, 2018)
Please see PDF file.